2019
DOI: 10.1063/1.5090387
|View full text |Cite
|
Sign up to set email alerts
|

PageRank: An alarming index of probable earthquake occurrence

Abstract: Here, we introduce PageRank (PR) in a seismic network as an appropriate alarming clue before the occurrence of the event to be worthwhile in hazard probabilistic evaluation of earthquakes. Studying PR changes of two main shocks in Iran and Italy by means of temporal and spatial windows reveals that their PR values increase drastically before the event, while there is no trend for other considered locations and/or other time intervals. Therefore, the PR value seems to be an appropriate index of a place inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This metric helps to provide an overview of connectivity in the entire network: The second famous centrality in the concept of earthquake network is PageRank [12,28]. PageRank is an algorithm used to assess the ranks of nodes in a network based on their connections' levels used in the Google search engine for ranking web pages for the first time [10].…”
Section: Resultsmentioning
confidence: 99%
“…This metric helps to provide an overview of connectivity in the entire network: The second famous centrality in the concept of earthquake network is PageRank [12,28]. PageRank is an algorithm used to assess the ranks of nodes in a network based on their connections' levels used in the Google search engine for ranking web pages for the first time [10].…”
Section: Resultsmentioning
confidence: 99%
“…We will compare the network characteristics number of nodes, average degree, betweenness, coreness, and entropy of the three networks. Since these measures' values have different orders of magnitudes, the log of these measures is used to distinguish better the differences [17]. In this regard, we first obtained the log of these measures and divided them to the most considerable log value for normalization, respectively.…”
Section: Evolutionmentioning
confidence: 99%
“…ey also discovered that the networks' topological characteristics change over time, corresponding to the large earthquakes [14][15][16]. Resaei et al [17] found that the PageRank value is an appropriate alarming clue before the event's occurrence, which is worthwhile in hazard probabilistic evaluation of earthquakes. However, the discovery of these laws is based on different network construction methods.…”
Section: Introductionmentioning
confidence: 99%